2022
DOI: 10.1108/tqm-06-2020-0139
|View full text |Cite
|
Sign up to set email alerts
|

Examining the role of dialogic communication and trust in donation-based crowdfunding tasks using information quality perspective

Abstract: PurposeThe study explores the role of dialogic public communication and information quality (IQ) in evaluating the operational performance of donation-based crowdfunding (DBC) tasks. These tasks are primarily used to support disaster relief operations. The authors also test the influence of cognitive trust and swift trust as moderating variables in explaining the relationship between both IQ and dialogic communication with operational performance.Design/methodology/approachThe authors used a primary survey to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 131 publications
0
26
0
3
Order By: Relevance
“…Donation-based crowdfunding or charitable crowdfunding can be framed as a type of philanthropy, namely giving monetary aid to the needy without any material reward (Behl et al, 2020). Donation-based crowdfunding is considered to be the smallest type compared with the other three types of crowdfunding in many regions (Zhao & Shneor, 2020).…”
Section: Donation-based Crowdfundingmentioning
confidence: 99%
“…Donation-based crowdfunding or charitable crowdfunding can be framed as a type of philanthropy, namely giving monetary aid to the needy without any material reward (Behl et al, 2020). Donation-based crowdfunding is considered to be the smallest type compared with the other three types of crowdfunding in many regions (Zhao & Shneor, 2020).…”
Section: Donation-based Crowdfundingmentioning
confidence: 99%
“…Moreover, the observed organizations tend to build up communities by applying crowdfunding techniques, which serve them as a starting point when launching new follow-up campaigns [167,168]. The use of external agencies to assist during crowdfunding campaigns, as outlined by Behl et al [111] and Du et al [112], could not be observed in the sample. A possible reason could be that the lean teams prefer to manage the campaign in-house, not spending funds on third-party support, which might not benefit the campaign to a large extent.…”
Section: Resultsmentioning
confidence: 93%
“…Among those who can choose the type of crowdfunding best-fitted to the need, besides the supporters and the campaign runners, additional stakeholders must be considered within the ecosystem [92,109]. External agencies support the success of the campaign with know-how and human resources [110][111][112]. Banks and external investors have an interest in knowing about the campaign, as well as the possible consequences, and more exposure means more parties being involved in critical decisions [97,98,113].…”
Section: Crowdfundingmentioning
confidence: 99%
“…In sociology, trust is divided into parts of emotion and reason, and the former is defined as emotional trust and the latter as cognitive trust [41]. Cognitive trust positively coordinates the relationship between the quality of information and the operational performance of crowdfunding [42]. A system quality means desirable characteristics of information systems, such as ease of use and learning, flexibility, credibility, and sophistication.…”
Section: Data Collection and Samplementioning
confidence: 99%